Towards an Objective Evaluation Layer: EEG-Based Assessment of Cognitive Engagement in AI-supported Immersive Cultural Heritage Experience - Ballı, Tuğçe; Fatih Yetkin, E. (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This study investigates EEG-based evaluation of immersive VR experiences using a publicly available dataset of 51 participants exposed to visual and audiovisual simulations of the Edzná Maya archaeological site. Frontal theta, occipital alpha, and engagement index (beta / (alpha + theta)) are examined as cognitive engagement markers. The findings provide a neurophysiological baseline for future neuroadaptive AI-driven heritage VR systems.